Image and its manufacturing in human communication vis-à-vis the translation profession: the image dynamism of the Polish sworn translator of the English language - Bielak, Marlena Iwona (Scripta Neophilologica Posnaniensia, 2019)
It is claimed that the Polish sworn translator in his/her translating activities is subject to a complex processes of image manufacturing. Based on some important contributions to the problem of image generation, it is shown that the Polish sworn translator’s practices within image generation suffer from being intuitive, not very careful and lacking cautious planning. It is also claimed that a successful image generation should be strengthened by proper cross-cultural conditioning.